A SOCIOLOGICAL ANALYSIS OF THE ROLE OF WOMEN IN THE MASS MOVEMENT AGAINST THE UMA OYA WATER PROJECT - Madushanka, M A D (6 th World Conference on Women’s Studies (WCWS 2020), 2020)
Uma Oya Multipurpose Development Project is one of the largest projects in Sri Lanka. The objective of this project was to fulfil the water and development needs of Hambantota district by diverting Uma Oya water to the Kirindi Oya reservoir. Environmental and social hazards have arisen with the creation of underground tunnels and water fountains. Subsequently a group of local affiliates have formed a front to protest against the project and its name is the “People's Front against Uma Oya Water Project”. The main research objective of this study was to identify the women's contradictions associated with the People's Front against the Uma Oya Water Project. The study was conducted in Heel-Oya Egodagama GN division in Bandarawela Divisional Secretariat. Out of 308 households, 30 households were selected by using purposive sampling technique and structured questionnaires and in-depth interviews were used to collect secondary data methodically. In discussing research findings, we should not forget examples that can be identified in a global context. Particularly in the Indian context, women's involvement in social movements such as Chipko and Narmada is significant. These social movements are based on Gandhism. In this, charisma-dominated female leadership can be identified and they have become the voice for the underprivileged women of the grassroots. According to this study, the majority of women have been affected by the Uma Oya water project and women have been the main victims. Women are also vulnerable because of the loss of livelihoods, which directly impacts on household economic instability. Two immediate factors that led to the escalation of women's resistance to the Uma Oya water project can be identified. One way is to address the domestic water consumption crisis. The other was the political mobilization of women to some extent by local political authorities. While women's activism is seen mainly in campaigns, there is little space for women in the organizational mechanism against the Uma Oya water project. It is thus understandable how the voice of women victims has been used as a means of political resistance in the mass movement against the Uma Water Project. Although women's representation in Sri Lanka's environmental movement is not very strong in comparison to Indian environmental movements, women's resistance to the Uma Oya water project marks an important turning point in Sri Lankan context.
Keywords: Mobilization; Uma Oya